2014
DOI: 10.1155/2014/378518
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Prediction Model for Normal Contact Damping of Joint Surfaces considering Friction Factors and Its Simulation

Abstract: To research the dynamic characteristics of the joint surfaces from the microperspective, the fractal prediction model of the normal contact damping of joint surfaces is established based on the "solid-gap-solid" contact model which was proposed by the author, tribology theory, and contact fractal theory. And the kinetic model of joint surfaces is improved to a certain extent. The influences of actual contacting area, friction coefficient, and the fractal dimension on the normal contact damping are revealed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Substituting Equations ( 18) and ( 23) into Equation (25) by F e = ΔF f , and the critical microcontact deformation considering friction can be written as…”
Section: Microcontact Area Of the Asperity Considering Friction Factormentioning
confidence: 99%
“…Substituting Equations ( 18) and ( 23) into Equation (25) by F e = ΔF f , and the critical microcontact deformation considering friction can be written as…”
Section: Microcontact Area Of the Asperity Considering Friction Factormentioning
confidence: 99%
“…According to literature [29], the critical deformation of the asperity in the elastic deformation stage is…”
Section: Variable Static Friction Coefficient Of Fractal Surfacementioning
confidence: 99%
“…25,26 Li and Pan established a fractal model for predicting the normal contact stiffness of dry friction on rough surface based on three-dimensional fractal function. [27][28][29][30][31] Based on contact mechanics and fractal theory, this paper deduces a model of static friction coefficient which changes with fractal dimension and normal load, and uses the variable static friction coefficient instead of the constant static friction coefficient based on Coulomb's law to analyze the effect of friction on the disc spring.…”
Section: Introductionmentioning
confidence: 99%
“…Majumdar and Bhushan 10 found that there was statistical selfsimilarity on each scale through the observation of the surface topography of components, thereupon the classic fractal contact model (M-B model) was given first based on fractal theory. 11 Tian et al 12 and Li et al 13,14 deduced the contact damping and contact stiffness model based on the M-B model. Since the contact damping model is based on two-dimensional fractal, it is not reasonable 15,16 in theory to describe the three-dimensional surface topography based on two-dimensional fractal curve, and the elastic-plastic transition mechanism of asperities is not considered.…”
Section: Introductionmentioning
confidence: 99%